Taxes, frictions and asset shifting - when Swedes disinherited themselves - Sebastian Escobar; Henry Ohlsson; Håkan Selin (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2019)
We study tax-driven intergenerational asset shifting using a salient tax discontinuity and rich data on both donors and recipients. When the Swedish inheritance tax was in place, heirs could lower their inheritance tax bills by passing on part of the inheritance to their children. We present evidence on strong and precise responses to this incentive. We quantify optimization frictions, and we show that they are small in this setting. Both intensive and extensive margin policy responses can be rationalized by a simple model in which agents face small frictions at the extensive margin. Descriptive evidence suggests that the policy response is associated with the abundant supply of cheap legal advice on tax planning.
Keywords: H21; H24; H26; 330; tax avoidance; tax rate elasticity; inheritance taxation; inter vivos gifts